S79 Predictors of response to mepolizumab in oral corticosteroid dependent severe asthma. (December 2018) - Kavanagh, JE; Green, L; Fernandes, M; Roxas, C; Jackson, DJ; Kent, B; d'Ancona, G
Abstract : Introduction: Patients with severe eosinophilic asthma (SEA) requiring maintenance oral corticosteroid (mOCS) to control their disease represent the most severe end of the asthmatic spectrum. Mepolizumab is a serum neutralising antibody against interleukin (IL)−5 with proven steroid-sparing efficacy in SEA requiring mOCS. Despite the appropriate phenotype, mepolizumab is not successful in all SEA patients, however to date no published data relating to possible responder characteristics in SEA exists to help guide physicians. Methods: A retrospective review of patients with SEA on mOCS who received mepolizumab for one year was carried out at a single tertiary asthma centre. Patients were divided into responders (defined as those who achieved ≥50% reduction in mOCS dose by 12 months) and non-responders (<50% reduction in mOCS dose). Baseline characteristics and outcomes at one year were compared between the two groups. Results: Fifty-two patients (61.5% female, mean age 52.9) with SEA on mOCS were included. 38/52 (73%) achieved ≥50% reduction in mOCS and were termed responders at one year. At baseline, compared to non-responders, the responder group had a significantly lower daily mOCS dose, better asthma control and were significantly less likely to be atopic (all p<0.05). A trend towards higher BMI in the non-responders was also observed (p=0.051). No differences in the baseline levels of T2 biomarkers was observed between responders and non-responders. Conclusion: In SEA requiring mOCS, a higher baseline OCS dose, higher ACQ6 and atopic status appear to be associated with a poorer response to mepolizumab. The trend observed with regards to higher BMI may suggest that the current 100 mg dose is insufficient for some patients. Further research is needed to understand whether the weight-based anti-IL-5 monoclonal antibody (mAb) reslizumab or the anti-IL5R mAb benralizumab may be effective in patients with SEA who have a suboptimal response to mepolizumab.